ACTIVATING HERITAGE TOURISM IN AKRE CITY BY APPLYING SUSTAINABLE ECOTOURISM APPROACHES - Malaika, Maha J.; Raswol, Layla (European Scientific Journal, ESJ, 2014)
Kurdistan Region has almost integrated tourism elements. It is one of the few areas that have diverse aspects of tourism, cultural combination and natural resources. Akre city is a mountainous city in North Iraq/ Kurdistan it is related administratively to Duhok governorate. Akre is a good example of various types of tourism such as natural, cultural, historic, treatment and eco-tourism; as well as its distinguished character in design and buildings. Through the last two decades the city faced neglect in preserving its heritage specially, and its construction generally. This research is a study of Akre city from touristic aspect, trying to highlight the most important features in the city heritage in order to activate the heritage touristic activity as a major contributor to cultural, economic, and social activities of the city.The research will study the existing situation ,and apply sustainable approaches by promoting heritage tourism as an attractive economic revitalization strategy, and one of the important means to develop historical , religious, and cultural tourism.